Influence of groundnut shell ash on strength and durability properties of clay. Issue 1 (2nd January 2016) - Sujatha, Evangelin Ramani; Dharini, K.; Bharathi, V.
Abstract : Groundnut shell ash, cement and their combinations are used as soil stabilizers in various percentages to improve the strength of locally available highly compressible clay soil. The effect of stabilizer in improving the strength of the soil is evaluated through change in consistency limits, compaction characteristics, undrained cohesion and modulus of elasticity. The durability characteristics of stabilised soil were studied based on the improvement of undrained shear strength for various days of curing by increasing the percentage of cement. Stabilised soil showed satisfactory improvement in strength and consistent durability characters. Groundnut shell ash and cement increased the optimum moisture content. There was a slight decrease in the dry density and modulus of elasticity of soil. These can be used as a viable economic alternative in construction of roads and for stabilising soil acting as bearing medium. The use of groundnut shell ash, an agricultural waste, helps in waste management and promotes sustainable development of local construction industry.